Perceptions of HIV risk and preventive measures among female students in Kolkata, India - Dutt, Sohini (Kansas State University, 2011)
According to the UNAIDS (2008) estimated, in 2005, that about 2.4 million Indians were living with Human Immunodeficiency Virus (HIV). This makes India one of the most HIV vulnerable countries in Asia and thus this problem cannot be ignored. The main purpose of this study was to gain an in-depth understanding of the awareness about HIV/AIDS preventive measures of female college students (in the 18 to 24 age group) in Kolkata, India, who were widely believed to be members of the low risk group. Specifically, the study measured the willingness to comply with HIV/AIDS preventive measures of the female college students. Few studies have investigated the perception, knowledge and opinions of female students regarding the effectiveness of HIV preventive measures, this study will add a new dimension to HIV/ AIDS literature. In order to assess the information available to the students an attempt has been made to examine the knowledge of the respondents concerning the modes of transmission of HIV and HIV prevention methods. The study also identified the significant sources of information that the respondents used to derive pertinent information enabling them to protect themselves from the virus. A host of variables (e.g. socio-economic and behavioral) have been studied in order to identify the factors influencing the willingness to comply with the preventive measures of these college students. From the results it was evident that religion, income and age play a role in influencing the students’ willingness to comply. This study has important public health implications because the information collected can be used to design HIV prevention interventions that can reduce HIV transmission in West Bengal and other states of India.
Keywords: AIDS in India; Medical Geography; AIDS Preventive Measures; Cultural Geography; Geography of Gender; Geography of Hazards; Gender Studies (0733); Geography (0366); Public Health (0573)